The Effect of Lavender Aromatherapy Towards Reducing Menatory Pain (Dysmenore) in Midwife Graduate Students in STIKES Mitra Husada Medan - Manurung, Herna Rinayanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Dysmenorrhea is menstrual pain that is often experienced by women during menstruation. During menstruation there is an increase in prostaglandin levels (PGE 2) which can cause pain during menstruation (dysmenorrhea). Dysmenorrhea can be treated in two ways, namely pharmacologically and non-pharmacologically. Aromatherapy Lavender is a non-pharmacological way to relieve menstrual pain (dysmenorrhea). The purpose of this study was to determine the effect of relaxation with lavender aromatherapy on reducing menstrual pain (dysmenorrhea) in undergraduate students of Midwifery at STIKes Mitra Husada Medan. Methods: This research is a type of pre-experimental research with the One Group Pretest-Post test design approach. The sample in this study were students who experienced dysmenorrhea as many as 20 respondents who were taken using purposive sampling technique, the test used was the Spearman Rank test with an error rate of p= 0.05. Results: In the study, the average menstrual pain of respondents before giving lavender aromatherapy on a scale of 4 were 15 respondents, while after giving decreased with a scale of 2 were 16 respondents. Based on the results of statistical analysis, it is found that ? value = 0.001 less than 0.05, this shows that Ho is rejected and Ha is accepted. Conclusion: From the results of the above research, it can be concluded that there is an effect of lavender aromatherapy on reducing menstrual pain (dysmenorrhea) in undergraduate students of Midwifery, STIKes Mitra Husada Medan. Suggestions for students are expected to be able to apply this non-pharmacological therapy to reduce menstrual pain (dysmenorrhea). And suggestions for STIKes Mitra Husada Medan in order to facilitate aromatherapy and a comfortable room for the implementation of therapy for students.Abstrak: Dismenore adalah nyeri haid yang sering dialami wanita saat menstruasi. Saat menstruasi kadar prostaglandin (PGE 2) meningkat, yang dapat menyebabkan nyeri saat menstruasi (dismenore). Dismenore dapat diatasi dengan dua cara yaitu farmakologi dan nonfarmakologi. Aromaterapi Lavender adalah salah satu terapi nonfarmakologi untuk meredakan nyeri menstruasi (dismenore). Tujuan penelitian ini adalah untuk mengetahui pengaruh relaksasi dengan aromaterapi lavender terhadap penurunan nyeri haid (dismenore) pada mahasiswa Sarjana Kebidanan STIKes Mitra Husada Medan. Metode: Penelitian ini merupakan jenis penelitian pre-Eksperimen dengan pendekatan One Group Pretest-Posttest design. Sampel dalam penelitian ini adalah mahasiswa yang mengalami dismenore sebanyak 20 responden yang diambil dengan menggunakan teknik Purposive Sampling, uji yang digunakan yaitu uji Spearman Rank dengan tingkat kesalahan p= 0,05. Hasil: Pada penelitian rata – rata nyeri haid responden sebelum pemberian aromaterapi lavender dengan skala 4 sebanyak 15 responden, sedangkan sesudah pemberian mengalami penurunan dengan skala 2 sebanyak 16 responden. Berdasarkan hasil analisis statistik di dapatkan ? value = 0,001 kurang dari 0,05, ini menunjukan bahwa Ho ditolak dan Ha diterima. Kesimpulan: Dari hasil penelitian diatas dapat disimpulkan bahwa terdapat pengaruh pemberian aromaterapi lavender terhadap penurunan nyeri haid (dismenore) pada mahasiswa Sarjana Kebidanan STIKes Mitra Husada Medan. Saran bagi mahasiswa diharapkan dapat mengaplikasikan terapi nonfarmakologi ini untuk mengurangi nyeri haid (dismenore). Dan saran bagi STIKes Mitra Husada Medan agar dapat memfasilitasi aromaterapi dan ruangan yang nyaman untuk pelaksanaan terapi bagi mahasiswa.